2022
DOI: 10.23887/paud.v10i1.47136
|View full text |Cite
|
Sign up to set email alerts
|

Permainan Puzzle Berbasis Multimedia Interaktif Untuk Menstimulus Kognitif Anak Usia Dini

Abstract: Kurangnya media pembelajaran yang digunakan guru dalam proses pembelajaran membuat anak kesulitan dalam memahami pembelajaran dan cepat merasa bosan. Pandemi juga membuat guru kesulitan dalam melaksankan proses pembelajaran. Jenis penelitian ini adalah penelitian pengembangan dengan menggunakan model pengembangan ADDIE. Penelitian ini bertujuan untuk mendeskripsikan rancang bangun dan mengetahui kelayakan permainan puzzle berbasis multimedia untuk menstimulasi kognitif anak usia dini. Subjek pada penelitian in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
5
0
2
Order By: Relevance
“…Previous research findings state that games that interest children will provide joy (Helfianti et al, 2021;Humaida & Suyadi, 2021;Yanthi et al, 2020). Other research also confirms that young children like games, impacting their ability to absorb information quickly (Faradisha & Ambara, 2022;Rekysika & Haryanto, 2019). The SKIDU (Sex Kids Education) game has proven to be a pivotal tool in teaching sex education to children aged 5-6 years, primarily because it transforms learning into an experience that feels authentic and engaging.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous research findings state that games that interest children will provide joy (Helfianti et al, 2021;Humaida & Suyadi, 2021;Yanthi et al, 2020). Other research also confirms that young children like games, impacting their ability to absorb information quickly (Faradisha & Ambara, 2022;Rekysika & Haryanto, 2019). The SKIDU (Sex Kids Education) game has proven to be a pivotal tool in teaching sex education to children aged 5-6 years, primarily because it transforms learning into an experience that feels authentic and engaging.…”
Section: Discussionmentioning
confidence: 90%
“…The research found that impact of digital media on children's learning activities is profound, necessitating careful consideration of its usage and the activities it promotes (Chassiakos et al, 2016;Hadders-algra, 2020;Pratiwi & Ismaniati, 2018). Other research found that game-based learning, particularly through digital means, has been shown to spark children's curiosity, encouraging them to discover innovative problem-solving methods within an engaging visual environment, thereby enhancing their learning satisfaction (Aryani & Ambara, 2021;Faradisha & Ambara, 2022;Fathimah & Ishartiwi, 2018). Digital learning games can significantly improve academic performance and foster essential skills like creativity, problem-solving, collaboration, and critical thinking (Behnamnia et al, 2020;Pratiwi & Ismaniati, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As technology develops, puzzles are also available in electronic form. The electronic form of puzzles also provides cognitive benefits for children, but its use requires an electronic device (Faradisha & Ambara, 2022). Electronic puzzles that require devices have limitations as the children can not put puzzles simultaneously at one time (Yuanita, Sabekti, and Silitonga, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Namely seas, rivers, swamps, and oceans. The development of teaching media requires a balance between the content of the material and the learning objectives (Faradisha & Ambara, 2022;Fathimah & Ishartiwi, 2018;Nuryani, 2020). The development of this material is intended to make it easier for children to recognize from an early age the diversity that exists in Indonesia in a simple way.…”
Section: Discussionmentioning
confidence: 99%
“…This study uses the ADDIE model with a systems approach. The essence of the approach system is dividing the lesson planning process into steps into logical sequences, using the output of each step (Faradisha & Ambara, 2022;Perangin-angin, 2017). The ADDIE model is divided into 5, including (1) Analysis, aims to find out the need for teaching materials on the theme Aku Cinta Indonesia for Kindergarten teachers who study at PG -PAUD FKIP UMS.…”
Section: Methodsmentioning
confidence: 99%